Ventricular tachycardia initiated by high energy cardioversion in a patient with an implantable cardioverter defibrillator. - Chinushi, M. (1997)
A transvenous implantable cardioverter defibrillator (ICD) was implanted into a 58 year old woman with idiopathic dilated cardiomyopathy who had drug refractory monomorphic ventricular tachycardia (VT). Antitachycardia pacing failed to terminate the VT; termination was attempted at 24 J, which was above the defibrillation threshold. When cardioversion at 24 J was delivered, VT with a different morphology and slower rate was reproducibly initiated. At 3 J, however, the original VT was successfully terminated without initiation of the slower VT. A new VT may be induced by high energy cardioversion. This may be a manifestation of the proarrhythmic potential of ICDs.